Survei Pembinaan Prestasi Klub Bulutangkis PB Moro Tresno Boja Kabupaten Kendal - hapsari, pingkan windi; Raharjo, Hermawan Pamot (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the coaching process carried out at the PB Moro Tresno badminton club by covering aspects of the organization, athletes, coaches and facilities and infrastructure. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out by means of observation, interviews, and documentation. Check the validity of the data with trust, transferability, dependence, and certainty. Analyzing the data is done by collecting data, reducing data, presenting data, and drawing conclusions.The results of the study are as follows: 1) the coaching of athletes carried out at PB Moro Tresno is quite good and directed. 2). The state of the organization managed by the PB Moro Tresno club management is quite good, can work well with club owners, administrators, coaches, athletes and athletes' parents, but improvements need to be made so that the organization's role can run optimally. 3). Achievements at the PB Moro Tresno club are quite good at the district and Pekalongan residency levels. 4) the facilities and infrastructure in the club are complete and adequate, although there are some shortcomings.